THE EFFECT OF PROFESSIONALISM, INDEPENDENCE, COMPETENCE, MOTIVATION AND JOB SATISFACTION ON AUDITOR PERFORMANCE (Study at the Jambi Province and Jambi City Inspectorate Offices) - Nelly Patria (Sean Institute, 2022)
This title of this research is analysis whether profesionalisme, independence, competence, motivation, and job satisfaction towards the performance auditor in Jambi Province Enviromental Inspectorate and Jambi City Inspectorate.The purpose of this study was (1)To analyze empirically whether profesionalisme, independence, competence, motivation, and job satisfactionsimultaneously influence on auditor performance.(2) To analyze empirically whether profesionalisme, independence, competence, motivation, and job satisfactionpartial effect on auditor performance.This study is a survey by distributing questionnaires directly to the respondents.The population in this study was the auditor in in Jambi Province Enviromental Inspectorate and Jambi City Inspectorate.Samples taken amounted to 86 auditors. Data were analyzed using multiple linear regression analysis and absolute difference.The results of this study show that (1) profesionalisme, independence, competence, motivation, and job satisfaction simultaneously influence on auditor performance (2) profesionalisme, independence, competence, motivation, and job satisfaction partial effect on auditor performance.